2015
DOI: 10.2215/cjn.07450714
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification in Patients with Nondialysis CKD over 3 Years

Abstract: Background and objectives Vascular calcification (VC) is common in CKD, but little is known about its prognostic effect on patients with nondialysis CKD. The prevalence of VC and its ability to predict death, time to hospitalization, and renal progression were assessed.Design, setting, participants, & measurements The Study of Mineral and Bone Disorders in CKD in Spain is a prospective, observational, 3-year follow-up study of 742 patients with nondialysis CKD stages 3-5 from 39 centers in Spain from April to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
137
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 36 publications
8
137
0
6
Order By: Relevance
“…In this issue of CJASN, Górriz et al assessed VC using the Kauppila and Adragao scores (16). VC occurs in both large elastic arteries and medium-size muscular arteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of CJASN, Górriz et al assessed VC using the Kauppila and Adragao scores (16). VC occurs in both large elastic arteries and medium-size muscular arteries.…”
mentioning
confidence: 99%
“…Górriz et al found that correlates of VC in predialysis CKD included age, diabetes mellitus, serum phosphorus levels, diastolic BP, pulse pressure, and waist circumference, as well as the use of anticoagulant therapy for models of medial calcification and statins for intimal calcification (16). The findings of associations with anticoagulant therapy and statins are unclear and require further investigation.…”
mentioning
confidence: 99%
“…OSERCE-2 was a 3-year follow-up prospective, observational, study which enrolled 742 adults with 3 to 5-stage CKD not on dialysis subjects attending 39 centres in Spain, to evaluate the effects of vascular calcifications and CKD-mineral bone disorders on mortality, hospitalization and kidney progression [32] . Inclusion criteria were age ≥ 18 years and CKD Stages 3-5.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…The study protocol of the OSERCE-2 study has been previously reported [32] . All patients were assessed at baseline for blood pressure measurement, lateral lumbar, pelvis and hands X-ray, an ankle brachial pressure index (ABPI) determination and laboratory blood sampling.…”
Section: Study Protocol and Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation